Análise da eficiência do tratamento de esgoto utilizando fossa ecológica TEVAP - Tanque de Evapotranspiração - Santos, Ana Maria dos (2025)
Water is an essential resource for human survival and for enabling the sustainable development of economic activities. The lack of accessible and adequate basic sanitation can trigger the discharge of domestic sewage into water bodies, implying a reduction in the quality of this resource that would be intended to supply communities. Alternative methods that aim to enable access to effluent treatment with low implementation costs are an advance for basic sanitation, thus being in harmony with the Sustainable Development Goals of the UN 2030 Agenda, directly with the sixth goal that refers to drinking water and sanitation and indirectly with the other 16 goals. The present study evaluated the efficiency of the evapotranspiration tank (TEvap) as a sustainable alternative for the treatment of domestic sewage in a family unit located in Aracaju/SE. The system, also known as an ecological septic tank, is a social technology based on the filtration and evaporation of effluent by the metabolism of plants, especially banana trees (Musa spp.). The methodology involved field visits, collections and laboratory analyses of effluent and soil samples, considering physical-chemical and microbiological parameters according to the guidelines of CONAMA Resolution 357/2005. The results indicated that the system promoted a significant reduction in microbiological load and partial removal of nutrients, especially nitrogen and phosphorus. Soil analysis showed limited benefits in fertility, suggesting the need for adjustments in complementary fertilization to optimize the development of banana plants. It is concluded that TEvap is a viable alternative for decentralized sanitation, contributing to the mitigation of water pollution and promoting a sustainable cycle of nutrient reuse.